Delayed-Damage Modelling for Fracture Prediction of Laminated Composites under Dynamic Loading - Allix, O.; Deü, J.-F. (Engineering Transactions, 1997)
The basic aspects of a damage meso-model with delay effects for laminated composites are presented. The applications concern fracture prediction under severe and multiaxial dynamic loading. In order to illustrate the possibilities and the mechanical significance of the proposed model for the prediction of rupture, especially the role of the delay effect, various simulations of one-dimensional wave propagation are performed. Then, a more complex finite element calculation is presented in order to show the ability of the model to predict the response of a composite structure until complete fracture.